Economic Inequality and Crime: A Socio-criminological Perspective - Aryal, Giri Raj (Journal of Development and Social Engineering, 2024)
This review paper explores the relationship between criminal activity and economic inequality, emphasizing how differences in income can influence people to commit crimes. The main concern is the historical and contemporary effects of economic inequality on social structures; wherein unequal resource distribution aggravates instability and criminal activity. Using a qualitative methodology, the study collects secondary data from criminological and sociological literature, impacted by theoretical viewpoints such social strain theory, Becker’s economic theory of crime, conflict theory, and relative deprivation theory. The findings are supported by evidence from a variety of international contexts, which shows a strong correlation between crime rates and economic disparity. Disadvantaged groups are particularly likely to engage in criminal activity because they face limited opportunities for genuine economic advancement. Systemic inequities, unemployment, and relative impoverishment are major contributory factors. Urbanization and young demography amplify these effects, albeit the effects varied depending on society. To reduce crime, the key takeaway highlights the significance of addressing economic inequality and suggests measures that promote equitable access to resources, education, and employment opportunities. By offering crucial insight into the socioeconomic elements that influence criminal conduct, these programs are key for fostering social cohesion, justice, and safer communities.